Genetic algorithms and genetic programming: modern concepts and practical applications - Affenzeller, Michael (Numerical Insights, 2009)
Genetic Algorithms and Genetic Programming: Modern Concepts and Practical Applications discusses algorithmic developments in the context of genetic algorithms (GAs) and genetic programming (GP). It applies the algorithms to significant combinatorial optimization problems and describes structure identification using HeuristicLab as a platform for al